2018
DOI: 10.1016/j.foodchem.2018.01.171
|View full text |Cite
|
Sign up to set email alerts
|

Rapid sucrose monitoring in green coffee samples using multienzymatic biosensor

Abstract: Amperometric biosensor utilizing FAD-dependent glucose dehydrogenase (FAD-GDH) for a specific sucrose monitoring in green coffee is described. FAD-GDH was co-immobilized with invertase and mutarotase on a thin-layer gold planar electrode using chitosan. The biosensor showed a wide linearity (from 10 to 1200 μM), low detection limit (8.4 μM), fast response time (50 s), and appeared to be O2 independent. In addition the biosensors exhibited a good operational (3 days) and storage (1 year) stability. Finally, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Some studies have shown that the content of sucrose increases continuously during the growth of coffee beans and the accumulation reaches its peak at maturity. Sucrose is one of the main components of green coffee, which affects the flavor and quality of coffee. , Some studies have shown that the sucrose content depends on coffee genotypes . However, other studies have found that the concentrations of sucrose, caffeine, and trimeline in green coffee do not seem to be significantly affected by the country of origin or genetic population .…”
Section: Results and Discussionmentioning
confidence: 99%
“…Some studies have shown that the content of sucrose increases continuously during the growth of coffee beans and the accumulation reaches its peak at maturity. Sucrose is one of the main components of green coffee, which affects the flavor and quality of coffee. , Some studies have shown that the sucrose content depends on coffee genotypes . However, other studies have found that the concentrations of sucrose, caffeine, and trimeline in green coffee do not seem to be significantly affected by the country of origin or genetic population .…”
Section: Results and Discussionmentioning
confidence: 99%
“…In this section, we review the main characteristics of molecular receptors, natural and synthetic, capable of selectively binding sucrose. Enzymes and proteins include: invertase (INV) [ 68 , 69 , 70 , 71 , 72 , 73 , 74 ], sucrose phosphorylase (SP) [ 75 , 76 ], Fluorescent Indicator Proteins (FLIP) [ 14 , 90 ], and lectins [ 91 , 92 , 93 , 94 , 95 ].…”
Section: Sucrose Quantification Using Molecular Recognition Methodsmentioning
confidence: 99%
“…Figure 3 shows the typical reaction sequences used in sucrose biosensors. For INV, the first step reaction transforms sucrose to glucose and fructose [ 68 , 69 , 70 , 71 , 72 , 73 , 74 ]. For SP, the first step reaction transforms sucrose to glucose 1-phosphate and fructose [ 75 , 76 ].…”
Section: Sucrose Quantification Using Molecular Recognition Methodsmentioning
confidence: 99%
“…The best cup quality conferred to C. arabica is attributed, in part, to its higher sucrose content in the dry and raw bean 33,57 , which is responsible for more than 90% of the oligosaccharides present in it 3 . However, according to Privat et al 25 although a good part of the sucrose is degraded during roasting, a fraction of it remains in the roasted bean (0.4-2.8% on a dry matter basis), contributing to the beverage flavor.…”
Section: Carbohydrates and Drink Qualitymentioning
confidence: 99%